2021
DOI: 10.1111/hdi.12982
|View full text |Cite
|
Sign up to set email alerts
|

The early start of hemoperfusion decreases the mortality rate among severe COVID‐19 patients: A preliminary study

Abstract: Background: Coronavirus disease-2019 (COVID-19)-related organ failure is partly related to a sepsis-like syndrome and extreme pro-inflammatory cytokine release, named cytokine storm. Therapeutic strategies that prevent the production of or remove the pro-inflammatory cytokines could potentially be an effective therapy in critically afflicted COVID-19 patients. Methods:In this clinical trial study, from April until June 2020, 68 COVID-19 patients (35 vs. 33 controls) with severe critical symptoms, and PaO 2 /Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
1
14
0
2
Order By: Relevance
“…This finding was consistent with different studies conducted in this field :10.31557/APJCP.2022.23.11.3735 Occurrence of ALCAM) and OSCC (Burandt et al, 2014;Lu et al, 2018;Sawhney et al, 2009;Tan et al, 2014;. However, in some other studies, no significant relationship was observed between ALCAM incidence and tumor size (Davies et al, 2008;Mikaeili et al, 2022;Tachezy et al, 2012). The significant relationship between ALCAM expression and tumor size can be related to the role of ALCAM in its proliferative stages and anti-apoptotic properties as well as the increase of ALCAM-ALCAM junctions in larger cell islets.…”
Section: Discussionsupporting
confidence: 90%
“…This finding was consistent with different studies conducted in this field :10.31557/APJCP.2022.23.11.3735 Occurrence of ALCAM) and OSCC (Burandt et al, 2014;Lu et al, 2018;Sawhney et al, 2009;Tan et al, 2014;. However, in some other studies, no significant relationship was observed between ALCAM incidence and tumor size (Davies et al, 2008;Mikaeili et al, 2022;Tachezy et al, 2012). The significant relationship between ALCAM expression and tumor size can be related to the role of ALCAM in its proliferative stages and anti-apoptotic properties as well as the increase of ALCAM-ALCAM junctions in larger cell islets.…”
Section: Discussionsupporting
confidence: 90%
“…In the review of Sanfİlippo F et al on hemoperfusion therapy in COVID‐19 patients, it was emphasized that hemoperfusion therapy was effective in reducing IL‐6 levels; however, more randomized controlled studies are needed on this subject 31 . A recent study, in which HA330 Disposable Hemoperfusion Cartridge (Jafron Biomedical Co., Ltd. China) was used, suggested that the early initiation of hemoperfusion significantly reduced mortality in critically ill COVID‐19 adult patients 32 . Another study with HA resin hemoperfusion cartridge (Model HA 280, Jafron Biomedical Co., Ltd.) reported that hemoperfusion at the inflammatory phase of the disease, especially before the intubation, reduced the need for mechanical ventilation, but hemoperfusion did not have any impacts on the duration of hospital and intensive care unit stay 33 .…”
Section: Discussionmentioning
confidence: 99%
“…31 A recent study, in which HA330 Disposable Hemoperfusion Cartridge (Jafron Biomedical Co., Ltd. China) was used, suggested that the early initiation of hemoperfusion significantly reduced mortality in critically ill COVID-19 adult patients. 32 Another study with HA resin hemoperfusion cartridge (Model HA 280, Jafron Biomedical Co., Ltd.) reported that hemoperfusion at the inflammatory phase of the disease, especially before the intubation, reduced the need for mechanical ventilation, but hemoperfusion did not have any impacts on the duration of hospital and intensive care unit stay. 33 Similarly, in a report of a 54-yearold male COVID-19 case, the application of CRRT/HP in the early stages of ARDS prevented the progression of the disease from moderate to severe ARDS, stabilizing and gradually enhancing the oxygen saturation, thus, removing the need for invasive mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) оценивают эффективность процедуры в ранние сроки нахождения в ОРИТ [7] (указывая не конкретные рамки, а динамику состояния, т. е., до ухудшения состояния, до потребности в механической респираторной поддержке), а в исследовании Haleh Mikaeili с соавт. (2021), оценивающем эффективность применения сорбции цитокинов в сравнении с контрольной группой пациентов без эфферентной терапии, средний срок начала лечения -7 дней с момента появления симптомов [8], что подтверждает данные, полученные в нашей работе.…”
Section: результаты и обсуждениеunclassified